SOCIAL INTERACTION AND THE CONCEPT OF PARENTING STYLE IN CHRISTIAN FAMILIES IN REALIZING TOLERANCE IN BANDA ACEH, INDONESIA - Khairil Fazal; Mawardi; Juwaini; Devi Farnanda (Malikussaleh Social and Political Reviews, 2026)
This study aims to examine the concept of parenting style in Christian families and its role in realizing religious tolerance attitudes in children. The study was conducted in East Lamteumen Village, Banda Aceh, a predominantly Muslim area. The focus of the research is directed at how parenting patterns in Christian family’s shape children's awareness of the importance of peaceful coexistence in a religiously and culturally plural society. The research methods used were qualitative to explore the parenting practices applied by Christian families in the location. The research uses a sociological approach with a focus on the theory of socialization and social interaction in the family, to analyze the three main concepts of parenting style that are analyzed including authoritarian, permissive, and democratic parenting. The results of the study show that the democratic parenting style adopted by Christian families is the most effective approach in fostering values ​​of tolerance because it encourages open communication. children's participation, and empathy for differences. Meanwhile, authoritarian parenting tends to hinder the formation of tolerant attitudes because it emphasizes obedience without space for dialogue. Obstacles identified in the parenting process include limited understanding of diversity, lack of tolerance in the surrounding environment, and lack of space for children to actively develop empathy. Therefore, in sociological theory and symbolic interaction, the family has an important role in socializing parenting patterns based on tolerance values is an important element in building an inclusive and harmonious society, especially for minority groups living in social contexts with different beliefs.